Source material from the VIR collection for hybrid breeding of multiple-ear maize - V. N. Boyko; E. B. Khatefov (Труды по прикладной ботанике, генетике и селекции)
Background. Expanding the genetic polymorphism of maize is an effective way to increase its productivity by involving multiple-ear genotypes in breeding.Materials and methods. In 2007, 596 maize accessions from VIR were assessed at the Kuban Experiment Station of VIR. In 2020, 52 hybrids between multiple-ear and single-ear maize lines were tested in the steppe zone of Kabardino-Balkaria at the site of the OTBOR Agrifirm. Useful agronomic traits were recorded, the coefficient of prolificacy (kmc) was calculated for the source lines and their hybrid progeny from crosses with a single-ear tester, and 52 parent lines were ranked according to the type of inheritance of the prolificacy feature.Results. Accessions that combined prolificacy with other useful agronomic traits were identified. The following accessions were selected for their plant height (score 5, 126–175 cm): k-8819, k-9054, k-15269, k-15355, k-15360, k-15331, k-15877, k-15442, k-15443, k-15445, k-8009, k-14344, k-15195, k-15226 and k-17385. Accessions that excelled in the height of the ear attachment for mechanized harvesting (score 5, 50–70 cm) were as follows: k-8819, k-15269, k-15355, k-15360, k-14394, k-14904, k-14979, k-14968, k-15292, k-15391, k-9289, k-15322, k-15439, k-15442, k-15443 and k-14344. Sources of the following traits were identified: long cob (score 9, > 20 cm): k-9054, k-4535, k-13730, k-14817 and k-14996; higher number of rows per ear (score 5–9, > 16 grain rows): k-14904, k-14979, k-14968, k-15442, k-15330, k-15322 and k-9257; and higher number of grains in a row (score 5–9, > 31 grains per row): k-14904, k-14996, k-15639, k-15353, k-15330, k-15322, k-15344, k-15281, k-15439, k-9357 and k-15237. Ranking 52 accessions according to the test cross results showed that 9 of them produced progeny of the maternal type (no more than one ear), 26 of the intermediate type (1.1–1.5 ears per plant), 11 of the paternal type (1.6–2,0 ears) and 6 of heterotic type (more than 2 ears).